Pregled merilnih metod za sprotno spremljanje usmerjenega strjevanja inženirskih materialov - Brunčko, Mihael (Materiali in tehnologije, 2001)
To achieve the required physical and mechanical properties of engineering materials, accurate monitoring of the microstructure evolution during the process of production is of crucial importance. This paper reviews some methods used for in-situ monitoring of the directional solidification process. Emphasis is given to the methods which allow nondestructive and online monitoring of the influence of parameters in the vicinity of the solidification front (?$G_SF$? - temperature gradient on the solidification front, ?$V_SF$? - velocity of the solidification front, ?$\deltaT_SF$? - supercooling of the solidification front, determination of the interface shape) during the directional solidification process. The methods can be used in research and in industrial applications.
Keywords: Metallurgical and Materials Engineering; metalurgija; strjevanje; merilne metode